Analysis of intercropping systems under rubber - Wijesuria Wasana; Iqbal S M M; Thattil R O; Yogaratnam N (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p28)
Analysis and interpretation of intercropping experiments are complex due to inclusion of two or more crops. Moreover, various types of experiments are involved in intercropping systems. Therefore, it is not to be expected that a single statistical approach suits all kinds of problems. The basic objective in all intercrop experiments is to assess biological or agronomic advantage accuring in any intercropping system. This paper therefore attempts to quantify the beneficial effects of intercropping with respect to the growth and yield of rubber using the available indices with some modifications to suit intercropping systems under rubber. Design, analysis and interpretation of intercrop experiments under rubber are also discussed.
Keywords: Intercropping; Rubber